2001
DOI: 10.1590/s0074-02762001000700004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution with soil-transmitted helminths in Sanliurfa, Turkey

Abstract: Soil transmitted helminth (STH) infection are endemic in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 1 publication
4
43
2
3
Order By: Relevance
“…Vegetables or fruit contaminated with Ascaris and Toxocara eggs represent important factors of transmission for rural and urban inhabitants (Vazquez Tsuji et al, 1997). In studies conducted by Ulukanligil et al (2001) in Sanliurfa (Turkey) A. lumbricoides eggs were detected in 11.0 % of unwashed vegetables tested. Choi and Lee (1972) found Ascaris eggs in 49.0 % of 147 lettuce samples that were collected from markets in Taegu (Korea).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetables or fruit contaminated with Ascaris and Toxocara eggs represent important factors of transmission for rural and urban inhabitants (Vazquez Tsuji et al, 1997). In studies conducted by Ulukanligil et al (2001) in Sanliurfa (Turkey) A. lumbricoides eggs were detected in 11.0 % of unwashed vegetables tested. Choi and Lee (1972) found Ascaris eggs in 49.0 % of 147 lettuce samples that were collected from markets in Taegu (Korea).…”
Section: Discussionmentioning
confidence: 99%
“…In the world, especially in developing countries, uncontrolled use of natural manure (e.g. cowpat, water from sources contaminated with human and animal excrement) to fertilize vegetables and fruits has been reported to be responsible for their high rates of contamination with helminth eggs (Takayanagui et al, 2000;Ulukanligil et al, 2001). In Turkey, helminth eggs were detected in 12 (5.9 %) of 203 unwashed samples of raw vegetables from wholesalers in Ankara (Kozan et al, 2005) where Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%
“…The increased demand, global sourcing and rapid transport of foods, especially soft fruit and salad vegetables, enhance both the likelihood of source contamination and survival of the transmissive stages of parasites pathogenic to man (Slifko, Smith, & Rose, 2000). In developing countries, especially, uncontrolled use of water from sources contaminated with human and animal faeces to irrigate such vegetables and fruits has been reported to be responsible for their high rates of contamination with helminth eggs (Guilherme et al, 1999;Takayanagui et al, 2000;Ulukanligil, Seyrek, Aslan, Ozbilge, & Atay, 2001). Considering the fact that a part of the vegetables grown in these developing countries are exported to the developed world, the threat that these contaminations cause to other countries cannot be overlooked (Robertson & Gjerde, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Low socioeconomic status, poor hygienic conditions, and lack of sanitary water supplies were reported to be factors that increased the prevalence of infection. Studies have demonstrated advanced contamination of water, soil, and vegetables, and a hazardous circulation between man and the environment [3,21]. In our study, the high rate of amebiasis in group II cases has been attributed to the risk factors present in this geographical region.…”
Section: Discussionmentioning
confidence: 48%